2011
DOI: 10.3802/jgo.2011.22.4.269
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of a high-risk group based on postoperative nadir CA-125 levels in patients with advanced epithelial ovarian cancer

Abstract: ObjectiveWe aimed to determine the ideal cut-off of nadir serum CA-125 level for prediction of progression free survival.MethodsAmong 267 patients who achieved complete remission after chemotherapy, the correlation between nadir CA-125 and progression free survival were compared among the subgroups classified according to the distribution of CA-125. The diagnostic odds ratio and area under the receiver operator characteristics curve were compared at various cut-off points.ResultsThe nadir CA-125 levels did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Using the same criteria, Kang et al [27] found a progression HR of 2.45 (95% CI, 1.55-3.88) in CA-125 > 10 U/ml Korean population. Gard et al [14] declared a progression HR was higher in patients with CA-125 > 15 U/ml; Kang et al [10] found a survival hazard ratio increasing for 12-18 U/ml and 18-35U/ml in Korean patients; and Altena et al [11] claimed an independent progression HR increasing to 1.51 (95% CI, 1.04-2.31 while CA-125 > 5 U/ml in a Netherlands population.…”
Section: Discussionmentioning
confidence: 99%
“…Using the same criteria, Kang et al [27] found a progression HR of 2.45 (95% CI, 1.55-3.88) in CA-125 > 10 U/ml Korean population. Gard et al [14] declared a progression HR was higher in patients with CA-125 > 15 U/ml; Kang et al [10] found a survival hazard ratio increasing for 12-18 U/ml and 18-35U/ml in Korean patients; and Altena et al [11] claimed an independent progression HR increasing to 1.51 (95% CI, 1.04-2.31 while CA-125 > 5 U/ml in a Netherlands population.…”
Section: Discussionmentioning
confidence: 99%
“…The primary therapy of EOC patients commonly ends after standard treatment, most including cytoreduction surgery and adjuvant chemotherapy. Several studies have suggested that the CA-125 level may be used to stratify high-risk recurrent patients [13]. As heterogeneous groups, different EOC pathological types present distinct clinical characteristics that indicate patient prognosis, including the CA-125 level.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, patients ranged from those with complete clinical response (CCR), as well as persisting and/or progressing disease, at the end of first line treatment to those with a recurrent disease after a PFS that varied from weeks to years. Most of these studies focused on advanced-stage EOC but not on its pathologic type [13-16]. Pathological heterogeneity of EOC was reported to influence the efficiency of the CA-125 level as an indicator in a single-institution study [12].…”
Section: Introductionmentioning
confidence: 99%
“…The DNA content is an important prognostic factor for epithelial ovarian cancer. Other important factors like residual disease, age, histology type and grade were not evaluated as well as other imunohistochemical factors including ARID1A, CA-125 and its new cut-off of 18 U/mL (32,40) . The study of these other factors would contribute to a better understanding of this cancer.…”
Section: Resultsmentioning
confidence: 99%